The Self-Compassion Scale Short Form for Children Aged 8–12: Validation of the Italian Version - Valentina Levantini; Iacopo Bertacchi; Antonella Magno; Gianluca Domenico Privitera; Alessia Rinaldi; Nicoletta Zara; Pietro Muratori (Children)
Background: Although self-compassion has been consistently linked to positive outcomes in adults and adolescents, only a few studies have explored self-compassion in children and early adolescents due to a lack of measures specifically designed for younger populations. Methods: The current study explored the psychometric properties of the Italian translation of the Self-Compassion Scale for Children (SCS-C) in a sample of 230 children (mean age = 10.52, SD = 1.33). Results: The results revealed a two-factor solution for our data, with a positive self-compassion factor and a negative self-compassion factor, which were shown to be internally consistent. The SCS-C scores correlated with the children’s mindfulness, self-esteem, and narcissistic traits in the assumed directions. Conclusions: Overall, our study preliminarily supports the reliability and validity of the Italian version of the SCS-C.